2019
DOI: 10.3390/cells8030276
|View full text |Cite
|
Sign up to set email alerts
|

CD44s Assembles Hyaluronan Coat on Filopodia and Extracellular Vesicles and Induces Tumorigenicity of MKN74 Gastric Carcinoma Cells

Abstract: CD44 is a multifunctional adhesion molecule typically upregulated in malignant, inflamed and injured tissues. Due to its ability to bind multiple ligands present in the tumor microenvironment, it promotes multiple cellular functions related to tumorigenesis. Recent data has shown that CD44 and its principal ligand hyaluronan (HA) are carried by extracellular vesicles (EV) derived from stem and tumor cells, but the role of CD44 in EV shedding has not been studied so far. To answer this question, we utilized CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…To study the effect of hyaluronan receptor CD44 on filopodial growth, two versions of human gastric cancer cell line MKN74, MOCK (CD44-negative) and CD44 (CD44 overexpression), were utilized ( Figure 6 A). The characterization of hyaluronan metabolism of MKN74 has shown that CD44 overexpression induces binding of hyaluronan to the plasma membrane, especially around filopodia [ 22 ]. However, the level of secreted hyaluronan was slightly higher in MOCK cells, the average amount being 2.5 ng/10,000 cells, while CD44+ cells produced 1.9 ng/10,000 cells of hyaluronan during 24 h [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To study the effect of hyaluronan receptor CD44 on filopodial growth, two versions of human gastric cancer cell line MKN74, MOCK (CD44-negative) and CD44 (CD44 overexpression), were utilized ( Figure 6 A). The characterization of hyaluronan metabolism of MKN74 has shown that CD44 overexpression induces binding of hyaluronan to the plasma membrane, especially around filopodia [ 22 ]. However, the level of secreted hyaluronan was slightly higher in MOCK cells, the average amount being 2.5 ng/10,000 cells, while CD44+ cells produced 1.9 ng/10,000 cells of hyaluronan during 24 h [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of hyaluronan metabolism of MKN74 has shown that CD44 overexpression induces binding of hyaluronan to the plasma membrane, especially around filopodia [ 22 ]. However, the level of secreted hyaluronan was slightly higher in MOCK cells, the average amount being 2.5 ng/10,000 cells, while CD44+ cells produced 1.9 ng/10,000 cells of hyaluronan during 24 h [ 22 ]. The FiloQuant analysis showed no significant difference in length ( Figure 6 B) or density ( Figure 6 C) of filopodia between the two cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD44 was also observed to be localized and accumulated in filopodia of gastric and squamous carcinoma cells together with HA, but CD44 does not appear to be essential in the formation of filopodia. 80,81 Downstream of CD44, activation of PKC, actin cytoskeleton reorganization, and ECM remodeling processes may be responsible for the regulatory roles of HA-CD44 pathway in promoting EC adhesion and migration during angiogenesis. We will discuss the molecular basis of the HA-CD44 pathway below.…”
Section: Cd44 In Tumor Angiogenesismentioning
confidence: 99%